Development Of Thematic Teaching Materials Based On The Project Model Based Learning (Pjbl) For Class Iv Students Of Elementary School - Rahmadani Rahmadani; Ayu Mustika Sari (Universitas Muhammadiyah Kuningan, 2021)
This research is a developmental research that aims to produce teaching materials based on the PjBL model that can be used by fourth grade students of SD 07 Koto Besar, Dharmasraya Regency as learning materials. Knowing the quality of teaching materials based on the PjBL model, validity, practicality, and effectiveness tests were conducted. Based on the validity test of the assessment conducted by media experts, materials and learning experts, the development model used is 4D consisting of 4 main stages, namely, define (delimiters), design (design), develop (development) and disseminate (dissemination). The development of teaching materials based on the PjBl model begins with an analysis of student needs, analysis of content standards followed by collection of learning material references, then drafting of teaching materials, and making teaching materials in the form of learning books. The teaching materials that have been made are consulted and assessed by experts, namely learning material experts, media experts, linguists, and large class students.